EFFICACY OF MULLIGAN MOBILISATION AS COMPARED TO MAITLAND MOBILISATION IN FEMALES WITH KNEE OSTEOARTHRITIS:A DOUBLE BLIND RANDOMIZED CONTROLLED TRIAL - Lalnunpuii, Angie; SARKAR, BIBHUTI; ALAM, SARFARAZ; EQUEBAL, DR; BISWAS, DR (International journal of therapies and rehabilitation research, 2017)
Both Mulligan and Maitland mobilisation along with supervised exercise program have been proved effective in decreasing pain, disability, improve range of motion and strength in patients having knee osteoarthritis. There is lack of literature comparing the efficacy of these two techniques in the female population. Conflicting results and lack of evidence puts this domain of research to be more explored. To find out and compare the efficacy of Mulligan mobilisation and Maitland mobilisation along with Supervised Exercise Program in females with Knee Osteoarthritis. 45 subjects with knee osteoarthritis were included and randomly assigned into 3 groups. Group-A (n=15) received Mulligan mobilisation along with supervised exercise program, Group-B (n=15) received Maitland mobilisation along with supervised exercise program and Group-C (n=15) received supervised exercise program alone thrice weekly for 4 weeks. Pain intensity during activities (measured using VAS), passive knee ROM (Universal goniometer), Maximum voluntary isometric strength of quadriceps (Handheld Dynamometer) and functional disability (WOMAC) were measured at pre-treatment, post treatment and at one week follow up. Statistically significant improvement was found in all the three groups for all outcome parameters (p<0.05). In between group analysis of post intervention and follow up data, Group-A shown significant improvement in VAS, ROM and WOMAC score compared to Group-B & Group-C but Quadriceps strength has shown insignificant changes in all the groups. Mulligan mobilisation along with supervised exercise program is more effective than Maitland mobilisation and supervised exercise program in relieving pain, increasing range of motion, strength and functional capacity in females with knee osteoarthritis.